THE PATHOLOGICAL EXAMINATION OF TWO CASES OF AMYOTONIA CONGENITA WITH THE CLINICAL DESCRIPTION OF A FRESH CASE - James Collier; Gordon Holmes (1909)
Journal Article THE PATHOLOGICAL EXAMINATION OF TWO CASES OF AMYOTONIA CONGENITA WITH THE CLINICAL DESCRIPTION OF A FRESH CASE Get access JAMES COLLIER, M.D., B.SC., F.R.C.P., JAMES COLLIER, M.D., B.SC., F.R.C.P. Physician 1St. George's Hospital, Physician to Out-patients to the National Hospital Search for other works by this author on: Oxford Academic PubMed Google Scholar GORDON HOLMES, M.D., M.R.C.P. GORDON HOLMES, M.D., M.R.C.P. Assistant Physician 2National Hospital; late Director of the Nervous Diseases Research Fund Search for other works by this author on: Oxford Academic PubMed Google Scholar Brain, Volume 32, Issue 3, November 1909, Pages 269–284, https://doi.org/10.1093/brain/32.3.269 Published: 01 November 1909